Novel oral anticoagulats for the treatment of left ventricle thrombosis: a systematic review and meta-analysis. (24th May 2021) - Serenelli, M; Vitali, F; Pavasini, R; Tonet, E; Pompei, G; Passarini, G; Tolomeo, P; Enriquez, A; Guardigli, G; Campo, G; Bertini, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: novel oral anticoagulants (NOACs) are not guideline-recommanded treatment for left ventricular thrombus. Purpose: the aim of this meta-analysis is to compare NOACs versus vitamin-K atagonsits (VKAs) efficacy in treating left ventricular thrombus (LVT). Methods: we systematically searched MEDLINE, Cochrane Library, Biomed Central, and Web of Science for trials comparing NOACs versus VKAs in the setting of LVT. Five studies, out of the 74 initially selected after first screening, were included in the meta-analysis. For the development of this meta-analysis, the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines were followed. The shortlisted studies were retrieved as full articles and appraised independently by two unblinded reviewers. The Mantel-Haensel method with a random effect model was used for the pooled analysis. The primary outcome was the occurrence of stroke and systemic embolism. Secondary outcome was occurrence of left ventricular thrombosis resolution during treatment. Results: 707 patients were included in the analysis for the primary outcome. Of these, 230 were treated with NOACs and 477 with VKAs. The pooled OR for the primary outcome was 0.71 (95% CI 0.18-2.86, I2 67%), thus showing similar effect in term of ischaemic protection. A total of 698 patients, 228 on NOACs and 470 on VKAs were included in the analysis of the secondary outcome. The pooled OR for the secondary outcome pooled OR 0.97, 95% CI 0.56-1.68, I2 46%. Conclusions and Relevance: NOACs seem to have a similar efficacy profile compare to VKAs and so they should be considered as an alternative treatment for left ventricular thrombosis. Large prospective randomized clinical trials are needed to confirm this exploratory finding.